Automated Lead Acid Battery Acceptance Testing System Module 1 - Zosa, Sidney Jr. A. (2005)
The objective of the project is to design and develop an automated system that performs characterization on a lead-acid battery, with the option of using the Interim Battery Acceptance Short Test Procedure or using the Life Cycle Test Procedure. The Interim Battery Acceptance Short Test Procedure makes use of the specification on Solar Home Systems which aims to characterize the sample battery with special regards on Discharging Current, End-of-Discharge Voltage, Battery Temperature and Capacity, and at the same time submit the result under the given criteria. A software program supervises the charge-discharge cycles basing its operation on the steps specified by any of the procedure. A regulated charger and discharger are also employed in the testing setup. The project also includes a graphical user interface that works on operating systems running Java, through the use of the parallel port.
Thesis (B.S. E.C.E.)--University of the Philippines Diliman.
Keywords: Lead-acid batteries; Interim Battery Acceptance Short Test Procedure; Battery testing system